2013
DOI: 10.1021/ac401576u
|View full text |Cite
|
Sign up to set email alerts
|

Zeolitic Imidazolate Framework-Based Electrochemical Biosensor for in Vivo Electrochemical Measurements

Abstract: This study demonstrates the first exploitation of zeolitic imidazolate frameworks (ZIFs) as the matrix for constructing integrated dehydrogenase-based electrochemical biosensors for in vivo measurement of neurochemicals, such as glucose. In this study, we find that ZIFs are able to serve as a matrix for coimmobilizing electrocatalysts (i.e., methylene green, MG) and dehydrogenases (i.e., glucose dehydrogenase, GDH) onto the electrode surface and an integrated electrochemical biosensor is readily formed. We syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
134
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(141 citation statements)
references
References 70 publications
4
134
0
3
Order By: Relevance
“…[3][4][5][6] Thus, ZIFs demonstrate great promise in various applications such as gas separation and storage, [6][7][8][9][10][11] chemical sensing, 12 and heterogeneous catalysis. [13][14][15][16][17] Driven by the increasing global energy demand, recent development in the field has extended the application of ZIF materials toward photocatalysis using visible light.…”
mentioning
confidence: 99%
“…[3][4][5][6] Thus, ZIFs demonstrate great promise in various applications such as gas separation and storage, [6][7][8][9][10][11] chemical sensing, 12 and heterogeneous catalysis. [13][14][15][16][17] Driven by the increasing global energy demand, recent development in the field has extended the application of ZIF materials toward photocatalysis using visible light.…”
mentioning
confidence: 99%
“…20 In addition, there are few studies to incorporate the functionality of achiral MOFs and its derivatives into enzyme biosensor applications. [24][25][26] To the best of our knowledge, until now no reports have been found regarding CMOFs for selective chiral detection. On the other hand, aiming at practical applications, the CMOFs must retain their structural integrity in both cases, the aqueous environment and the removal of the guest molecules trapped in the channels for creating empty pores and accessible metal sites.…”
mentioning
confidence: 99%
“…[ 34 ] Chen et al showed that ZIF-67 was used as a promising formaldehyde gas sensor. [ 35 ] Wang et al reported the water oxidation electrocatalysis by a zeolitic imidazolate framework.…”
mentioning
confidence: 99%
“…All diffraction peaks correspond well to a pure cubic ZIF-67 and match well with the simulated as well as the published results. [ 34 ] ZIF-67 has three-dimensional zeolite-like structure with SOD topology as shown in the inset of Figure 1 a. In addition, gas sorption properties of the as-prepared ZIF-67 samples are also studied.…”
mentioning
confidence: 99%